Protection of urban features during urbanization based on the roles of springs in Jinan. Issue 2 (3rd April 2017) - Wang, Xueqin; Wang, Chengxin; Wang, Botao; Liu, Shenghe; Song, Jinping
ABSTRACT: Thirty-seven years since reform and opening up, China has sustained rapid economic growth and urbanization. However, there was inadequate protection of natural, historical, and cultural heritage, especially in the past 17 years, which led to the outcome that urban and rural construction lacked features. To rebuild our urban features during urbanization, and avoid destroying them, we should probe into the reason of lacking features and how to protect them. Therefore, taking Jinan City as an example, this paper explored the crisis and its causes of urban characteristics during the period of rapid urbanization based on discussing roles of spring features, including economic effects, social effects, ecological effects and so on. What is more, this paper listed and analyzed those protection measures taken by Jinan. The results showed that spring groups spewed again and kept for 8 years through those measures, which meant that urban characteristics restored. Thus, Jinan City provides successful and significant reference for other cities in restoring urban features during urbanization construction. Also, the author deemed that cities could recollect their urban features as long as they take reasonable measures.